Forgers and critics : creativity and duplicity in western scholarship - Grafton, Anthony (Princeton University Press, 2019)
The close links between forgery and criticism throughout historyIn Forgers and Critics, Anthony Grafton provides a wide-ranging exploration of the links between forgery and scholarship. Labeling forgery the "criminal sibling" of criticism, Grafton describes a panorama of remarkable individuals-forgers from classical Greece through the recent past-who produced a variety of splendid triumphs of learning and style, as well as the scholarly detectives who honed the tools of scholarship in attempts to unmask these skillful fakers. In the process, Grafton discloses the extent, the coherence, and the historical interest of two significant and tightly intertwined strands in the Western intellectual tradition.